Melawan Hegemoni Media dengan Strategi Komunikasi Berpusat pada Masyarakat - YudhiMario Antonius Birowo (Jurnal ILMU KOMUNIKASI, 2005)
Abstract : The present form and structure of mass media has become the most effective tool in the pursuit of globalization and hegemony of ruling elites. Consequently the mass media do not provide a space for people to participate in the process of production, which causes a gap between the mass media and people. Therefore the mass media cannot play a role in social change because it does not have roots within the people. To fulfill this gap, grass-roots people need alternative media which help them to be heard. One type of alternative media is community radio. This media started in the 1940s with the first community radio stations in Colombia and Bolivia. In Indonesia, this media started in 1990s. The existence of community radio cannot be separated from civil society movement.